Managing NPD: Cost and Schedule Performance in Design and Manufacturing - Bajaj, Akhilesh; Kekre, Sunder; Srinivasan, Kannan (Management Science, 2004)
In this field study, conducted at a leading avionics guidance systems manufacturer, we gathered primary data on time and cost performance of both the design and manufacturing phases of new product development (NPD). We modeled the impact of the management levers relating to oversight, the intensity of design specialization, and the level of interaction with the customer. The study highlights the necessity of leveraging the interdependencies between the design and manufacturing phases in NPD.